Neuroimaging, genetic, and enzymatic study in a Japanese family with a GBA gross deletion. (April 2019) - Ichinose, Yuta; Ishiura, Hiroyuki; Tanaka, Masaki; Yoshimura, Jun; Doi, Koichiro; Umeda, Takako; Yamauchi, Hajime; Tsuchiya, Mai; Koh, Kishin; Yamashiro, Nobuo; Mitsui, Jun; Goto, Jun; et al.
Abstract: Introduction: Glucocerebrosidase gene ( GBA ) variants are associated with Parkinson's disease (PD) and dementia with Lewy bodies (DLB). The molecular mechanisms underlying these diseases with GBA variants, however, are not well understood. In order to determine the effect of a deletion mutation in GBA, we performed a neuroimaging, genetic, and enzymatic study in a Japanese family with a gross deletion of exons 3 to 11 in GBA . Methods: We performed [ 123 I] FP-CIT SPECT and [ 123 I] N -isopropyl- p -iodoamphetamine SPECT (IMP-SPECT), and determined GBA expression and glucocerebrosidase (GCase) activity in leukocytes in two GBA -associated PD patients and nine unaffected individuals (including four mutation carriers) in a Japanese family with a heterozygous gross deletion mutation in the GBA gene. Results: The two PD patients and two of the four clinically unaffected carriers showed decreased [ 123 I] FP-CIT uptake. IMP-SPECT showed a pattern like that in DLB in one patient. When we compared PD patients with GBA mutations with clinically unaffected carriers, there was a poor correlation between the development of PD and the expression level of GBA or GCase activity. Conclusion: We confirmed the gross deletion mutation in the GBA gene, which appeared to be associated with the PD or reduced [ 123 I] FP-CIT in this family. However, since we cannot conclude whether a reduction of GCase activity is directly correlated with the pathogenesis of PD or not, longitudinal follow-up of this family is needed. Highlights: This is the first report of a family with a GBA gross deletion. There is a poor correlation between the development of PD and remaining GCase activity. Some unknown pathogenetic factors may affect the development of GBA -PD besides GCase.